Glasswort as a Strategic Crop in Coastal Wetlands: Intercropping Results with Swiss Chard - Anna Rita Bernadette Cammerino; Michela Ingaramo; Vincenzo Rizzi; Maurizio Gioiosa; Massimo Monteleone (Agronomy)
The Mediterranean region is experiencing severe droughts and unprecedented high temperatures. In terms of salinity, about 18 million ha of land, or 25% of the total irrigated area in the Mediterranean, is salt affected. The use of halophytes as intercropping species to mitigate the effects of salt stress is attractive. Halophytes have a great capacity to maintain their productivity in this extreme environment, thus supporting climate-appropriate agriculture. The aim of this study was to evaluate the productivity of Salicornia europaea L. subsp. ramosissima (glasswort) under field conditions and high soil salinity, grown as a sole crop (monocropping) and as a companion crop (intercropping) with Beta vulgaris L. subsp. cicla (Swiss chard) in a 1:1 cropping pattern. The field trials were conducted in the coastal wetland “King’s Lagoon”, a private nature reserve in the Apulia/Puglia region (southern Italy), during two consecutive spring–summer seasons in 2023 and 2024 and under different management conditions of irrigation and fertilization. These were performed to test for possible interaction effects. The results showed that both glasswort and chard can be grown sustainably under slightly saline conditions (ECe range 4–8 dS m−1). In contrast, strongly saline conditions (ECe > 16 dS m−1) were prohibitive for chard, both as a sole crop and as an intercrop, but were largely beneficial for glasswort. Swiss chard can benefit from intercropping with glasswort when soil salinity is still tolerable (6.9 dS m−1), showing an LER (Land Equivalent Ratio) ≥ 1.19. Meanwhile, glasswort did not significantly improve the growth of the companion crop (Swiss chard) when the soil was considerably saline (16.6 dS m−1). Higher LER values were observed when the contribution of chard to the intercrop performance was significantly greater than that of glasswort, i.e., under slightly saline conditions. This means that glasswort can have a significant positive effect on chard growth and productivity as long as soil is still moderately saline. Glasswort can therefore be considered a valuable model crop in extreme environments. The integration of glasswort (possibly together with other local halophytes) into diversified cropping systems on saline marginal soils is a promising sustainable agricultural practice in environmentally fragile areas such as wetlands, swamps, brackish areas, and marshes.